Can Renewable Energy Offset the Economic Costs of Loadshedding in the Eastern Cape Province of South Africa? A Social Accounting Matrix Analysis - Kavese, Kambale; Anyikwa, Izunna; Phiri, Andrew (International Journal of Energy Economics and Policy, 2026)
Reliable electricity supply is a key driver of economic growth, employment, and social welfare, yet persistent load shedding continues to constrain South Africa’s development, particularly in the Eastern Cape. The province’s high unemployment, low investment, and reliance on energy-intensive sectors make it especially vulnerable to electricity shortages. Renewable energy investments through the Independent Power Producers Procurement Programme (IPPPP) offer a pathway to stabilize supply, stimulate economic activity, and promote sustainable growth. Using a Social Accounting Matrix (SAM)-based multiplier model, this study quantifies the economy-wide effects of two scenarios: the contraction caused by load shedding and the expansionary fiscal injection of R21.9 billion into renewable energy. Our analysis captures direct, indirect, and induced impacts across sectors, providing evidence on how renewable energy can not only offset losses but also generate broader economic and employment benefits in the Eastern Cape.